PERAN PERBANKAN SYARIAH DALAM UMKM UNTUK MENGEMBANGKAN EKONOMI INDONESIA - Pramesti Harmar (Nurul Jadid University, 2021)
This research is descriptive qualitative using literature study obtained from several sources of secondary data, in the form of theories, reports, research results and others.It aims to analyze the role of Islamic banking in UMKM to Indonesia's economic growth. Crisis conditions occurred during the period 1997 to 1998, only the UMKM (Micro, Small and Medium Enterprises) sector was able to remain strong after the economic crisis. The number of UMKM did not decrease, instead their growth increased . The efforts of Islamic banking in developing the country's economy include providing financing through micro, small and medium enterprises. As the government pays attention to the development of UMKM in Indonesia, sharia banking also participates in empowering these UMKM which will then stimulate economic sectors and spur economic growth.